Can Digital Technology Bridge the Classroom Engagement Gap? Findings from a Qualitative Study of K-8 Classrooms in 10 Ontario School Boards - Jessica Rizk; Scott Davies (Social Sciences, 2021)
This study examined impacts of digital technology on a key component of the socioeconomic gap in education—gaps in student classroom engagement. Whereas print literacy has long been a source of such gaps, newer “digital divide” theories claim classrooms that use digital technology are perpetuating them further. However, these claims are not grounded in close empirical observation and may now already be dated. We aimed to advance understandings of the impact of digital technology on student engagement by examining robotics, tablets, and smart board usage across a range of classrooms, using a conceptual framework that blends theories of interaction ritual chains (IRC) and cultural capital (CC). Data came from observations and interviews with teachers and students in K-8 classrooms across 10 Ontario school boards. We report three major findings. First, almost all students across socioeconomic strata engaged easily and enthusiastically with digital technology. Second, technology spawned new classroom rituals and cultural valuations. Third, digital technology provided connections between school dictates and students’ peer-based and home lives. We argue that digital technology has the potential to narrow classroom engagement gaps that are generated by conventional print media. We end by discussing avenues for future research.